Methodological mimesis and the value of pharmaceutical failures - McGoey, L (2009)
Recent controversies over the safety of drugs such as Vioxx, a painkiller manufactured by Merck, and Seroxat, an SSRI antidepressant manufactured by GlaxoSmithKline, have led to a consequence that at first seems entirely positive: they have attracted more attention to the suppression of negative clinical trial data by industry and academic researchers, helping to establish clinical trial registries where randomized controlled trials (RCTs) must be registered at their outset. In this paper, through a focus on debates over the safety of selective serotonin reuptake inhibitor (SSRI) antidepressants such as Seroxat, I examine recent efforts to provide more public access to clinical trial data, documenting how, despite declarations of their commitments to openness, pharmaceutical companies have found ways to evade the need to publicly disclose trials. Secondly, I suggest the emphasis on securing more access has fostered the adverse effect of deflecting attention from methodological limitations within studies that are widely available. Drawing analogies to work by Bourdieu, I argue that a paradoxical consequence of the demand for more access is the tendency to solidify faith in the moral authority of RCTs, something that inadvertently strengthens the authority of those, such as regulators and industry groups, which withheld RCT data to begin with. I suggest it is the very limitations of RCTs – their inadequacies in producing reliable evidence of clinical effects – that help to strengthen popular and scientific assumptions of their superiority as methodological tools. This point sheds light on the question of why systems widely recognized to be ineffective often assume greater authority at the very moment when people speak of their dysfunction.